ANALYSIS OF LEGAL TERMINOLOGY TRANSLATION FROM ENGLISH INTO UZBEK LANGUAGE (Ustozlar uchun, 2026)
This thesis examines the translation of legal terminology from English into Uzbek. The study focuses on terms that are frequently found in legislation, contracts, court-related documents, and official legal communication. The main purpose is to identify how meaning, legal function, and contextual accuracy are preserved during translation. The research is based on comparative, descriptive, contextual, and terminological analysis. English legal terms are compared with their Uzbek renderings in order to show cases of full equivalence, partial equivalence, descriptive translation, and borrowing. The study finds that legal terms cannot always be translated word for word because English and Uzbek belong to different linguistic systems and are connected with different legal traditions. The most reliable translation is usually achieved when the translator considers not only the dictionary meaning of a term but also its legal role in a specific text. The thesis concludes that accuracy in legal terminology translation is essential for clear legal understanding and for the practical validity of translated documents.